Prawo własności nieruchomości w obliczu regulacji prawa górniczego w Królestwie Polskim z 1817 i 1870 roku - Filipiak, Zbigniew; Gac, Andrzej (Studia Iuridica Toruniensia, 2012)
<!--[if gte mso 9]> <![endif]--> The article presents the conception of mining property in the Kingdom of Poland on the basis of two Acts of 1817 and 1870. The authors of the article discuss also the outline of changes of the National Mining Law in the previous years. In the Middle Ages, the right to extract raw materials and ore (known as the mining regalia), just like in the other countries of Europe, was the kings’ previlege and at the same time an essential source of their profi ts. With the passing of time, mining rights became the subject of the royal privilege (of which the church organizations were the main benefi ciaries). The turning point was the beginning of the elective kings era when the Polish nobility by virtue of the Henrican Articles (1573) obtained a right to own raw materials extracted from their private estates. As far as the extracting industry (especially salt industry) was concerned, it was still concentrated mainly in the royal estates. Another change was related to the period of the Partitions of Poland. Under Prussia and Austria rule all ore became the public good again, whereas in the Kingdom of Poland under Russia rule, plenty of interesting regulations in the Mining Law were introduced due to the inspiration from the French solutions. The Acts of 1817 and 1870 introduced a new vision of the previous institution known (also in Poland) as liberty of mining. In accordance with it, on the strength of governmental concession, one could search and extract ore without the permission of the land owner. The Act of 1870 initiated the notion of paraphernal mine property which constituted additional stimulus for the industrial development of the Kingdom of Poland. It was adopted from France, although in Polish version it was given an original and unique form, present mainly in its establishment procedure, which respected the rights of private property of interior and surface of land, arising from the Napoleonic Code. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->